Synthesis and Performance of ZnAl@Layered Double Hydroxide Composites with Eucheuma cottonii for Adsorption and Regeneration of Congo Red Dye - Wibiyan, Sahrul; Royani, Idha; Lesbani, Aldes (Indonesian Journal of Environmental Management and Sustainability, 2024)
This study investigates the synthesis and characterization of ZnAl-layered double hydroxide (ZnAl@LDH) composites modified with Eucheuma cottonii (EC) for the adsorption and regeneration of congo red (CR) dye. The ZnAl@LDH was synthesized using a co-precipitation method, and the composite with EC was prepared via hydrothermal techniques. The structural properties of the composites were analyzed using XRD and FTIR. Adsorption experiments were conducted to determine the effects of pH, contact time, concentration, and temperature on dye removal. The adsorption kinetics followed the pseudo-second-order (PSO) model, while the isotherm data best fitted the Freundlich model, indicating multilayer adsorption. The ZnAl@EC composite demonstrated superior adsorption capacity (243.902 mg/g at 40 °C) compared to ZnAl@LDH and EC. Thermodynamic studies revealed that the adsorption process was spontaneous and endothermic for ZnAl@LDH and EC but exothermic for ZnAl@EC. The regeneration study showed that ZnAl@EC retained significant adsorption capacity even after seven cycles, indicating its potential for practical applications in wastewater treatment.